RESEARCH OF MULTI-RESISTANT GRAM NEGATIVE BACTERIA IN THE ORAL CAVITY OF PATIENTS SEEN IN DENTAL CLINICS - Monteiro Chaves Bernardo, Bárbara; Laís Pinto Soares, Jhéssica; Tauanny Souza Silva, Emily; Gabriele Martins Soares, Victória; Ananias de Lima, Camila; Rodrigues Martins, Lamartine; Tavares Jácome Júnior, Agenor (Health and Society, 2022)
Introduction: Gram-negative bacteria are the main cause of infections ranging from pneumonia to bloodstream infection. In the oral cavity, there may be microorganisms associated with systemic and opportunistic infections. In addition, the irrational use of antibiotics related to odontogenic infections will promote the colonization of these microorganisms and contribute to antimicrobial resistance. Objective: To investigate the presence of multidrug-resistant gram-negative bacteria in the oral cavities of patients in a dental clinic. Material and Methods: The characteristic of the study is to be observational, with a laboratory and cross-sectional design. A sample of 60 patients from all Asces-Unita dental clinics was used. Samples were obtained through a swab smear on the patient’s oral mucosa. The technique for laboratory analysis follows the methodology of Winn et al. Antibiogram was performed according to the Kirby-Bauer technique. The antibiotics used followed the indications provided by CLSI 2021 and BrCAST 2021. This is a study using descriptive statistics. Results and Discussion: From 60 bacterial isolates obtained, 15 samples of gram-negative bacteria were obtained, mostly Pseudomonas aeruginosa 6 (40%), Klebsiella pneumoniae 5 (33.3%), Enterobacter sp 1 (6.66%), Citrobacter sp 1 (6.66%) and Proteus vulgaris 2 (13.33%). Multidrug resistance was observed in 20% of Klebsiella pneumoniae cases, in 83.3% of Pseudomonas aeruginosa cases, in 100% of Proteus vulgaris cases. Nowadays, antimicrobial resistance is the main problem in Intensive Care Units (ICU), the excessive use of antibiotics in communities and hospitals directly contributes to the development of bacterial resistance.Conclusion: Multidrug-resistant gram-negative bacteria were isolated in the oral cavity of patients seen at a dental clinic. In view of this finding, it is important to review the antibiotic treatment used to combat infections caused by gram-negative bacteria, based on laboratory identification and the use of an antibiogram.